Optical properties of diamond-like carbon films prepared by pulsed laser deposition onto 3D surface substrate. (3rd April 2021) - Lu, Yimin; Huang, Guojun; Wang, Sai; Xi, Lin; Mi, Chaowei; Wang, Shuyun; Cheng, Yong
ABSTRACT: It is difficult to grow uniform film by pulsed laser deposition because the spatial distribution of the laser-induced plume is a forward-directed cone-shape. A 3D-motional deposition setup was founded, and the correlative mathematical model of the film thickness on the 3D curved surface was deduced. Based on simulation and optimization, the diamond-like carbon (DLC) film was grown onto the large curved silicon substrate. According to the infrared transmittance spectra, the optical constants of the DLC film samples at different regions on the curved substrate were similar, indicating that the DLC film prepared onto the curved surface was homogeneous. Meanwhile, the deviation of average transmittance in the medium infrared band was below 2.3%, which could improve the imaging performance of the infrared detection. This research is useful to expand the application of the pulsed laser deposition in the optical field.